Assessing the parent–infant relationship: a two-stage, COSMIN-informed systematic review evaluating clinician-rated measures - Shone, Isabelle; Gregg, Lynsey; Wittkowski, Anja (Frontiers in Psychiatry, 2025)
BackgroundThe parent–infant relationship is important for healthy infant development. Parent–infant assessments can aid clinicians in identifying any difficulties within the parent–infant relationship. Meaningful, valid, and reliable clinician-rated measures assist these assessments and provide diagnostic, prognostic, and treatment indications. Thus, this review aimed to (a) provide a comprehensive overview of existing clinician-rated measures and their clinical utility for the assessment of aspects of the parent–infant relationship and (b) evaluate their methodological qualities and psychometric properties.MethodsA systematic search of five databases was undertaken in two stages. In Stage 1, relevant clinician-rated parent–infant assessment measures, applicable from birth until 2 years postpartum were identified. In Stage 2, relevant studies describing the development and/or validation of those measures were first identified and then reviewed. Eligible studies from Stage 2 were quality assessed in terms of their methodological quality and risk of bias; a quality appraisal of each measure’s psychometric properties and an overall grading of the quality of evidence were also undertaken. The COnsensus-based Standards for the selection of health Measurement INstruments methodology was used.ResultsForty-one measures were eligible for inclusion at Stage 1, but relevant studies reporting on the development and/or validation of the parent–infant assessments were identified for 25 clinician-rated measures. Thirty-one studies reporting on those 25 measures that met inclusion criteria were synthesised at Stage 2. Most measures were rated as “low” or “very low” overall quality according to the Grading of Recommendations Assessment, Development and Evaluation approach. The most promising evidence was identified for the Mother–Infant/Toddler Feeding Scale, Tuned-In Parenting Scale, and Coding Interactive Behaviour Instrument.ConclusionsThere was a notable diversity of measures that can be used to assess various aspects of the parent–infant relationship, including attunement, attachment, interaction quality, sensitivity, responsivity, and reciprocity. The quality of methodological and psychometric evidence across the reviewed measures was low, with 76% of measures having only one study supporting the measure’s development and/or validation. Thus, further research is needed to review the psychometric properties and suitability as assessment measures.